«Once upon a wartime...», a pedagogical lesson of Angelo Patri (1876-1965) - Carmen Petruzzi (University of Bologna, 2023)
As a means to inform contemporary discourse on education in emergency contexts, it can be useful to consider the experiences of the past in times of crisis. Angelo Patri (1876-1965), an Italian-American teacher and school principal, was able to converge his pedagogical thinking and experience in the formulation of concrete answers to the families affected by World War II. Your Children in Wartime (1943) is a skillful work on the necessary roles of the school, family, community, and even the children themselves, in the growth path during times of conflict and confusion. As such, it still provides an excellent manual for teachers of our current days, as they attempt to cope with these extraordinary times in their own careers and in their public service. The current essay returns to the historical period of Patri's writing, elaborating on the basic principles expressed in his volume Your Children in Wartime.